2009
DOI: 10.3354/dao02023
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships in the family Alloherpesviridae

Abstract: Phylogenetic relationships among herpesviruses (HVs) of mammals, birds, and reptiles have been studied extensively, whereas those among other HVs are relatively unexplored. We have reconstructed the phylogenetic relationships among 13 fish and amphibian HVs using maximum likelihood and Bayesian analyses of amino acid sequences predicted from parts of the DNA polymerase and terminase genes. The relationships among 6 of these viruses were confirmed using the partial DNA polymerase data plus the complete sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
147
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(157 citation statements)
references
References 85 publications
10
147
0
Order By: Relevance
“…The first clade comprises anguillid and cyprinid herpesviruses, which possess large genomes (245-295 kb). The second clade comprises ictalurid, salmonid, acipenserid, and ranid herpesviruses, which have smaller DNA genomes (134-235 kb) [86]. Interestingly, KHV resembles the poxviruses by the presence of thymidylate monophosphate, ribonucleotide reductase and a B22R-like genes [38].…”
Section: Virus Taxonomymentioning
confidence: 99%
“…The first clade comprises anguillid and cyprinid herpesviruses, which possess large genomes (245-295 kb). The second clade comprises ictalurid, salmonid, acipenserid, and ranid herpesviruses, which have smaller DNA genomes (134-235 kb) [86]. Interestingly, KHV resembles the poxviruses by the presence of thymidylate monophosphate, ribonucleotide reductase and a B22R-like genes [38].…”
Section: Virus Taxonomymentioning
confidence: 99%
“…Based on terminase gene's taxonomy-tree, the virus of oyster is a clade a part from the other Herpesvirus. In Figure 2 herpesviruses dataset and phylogenic tree from Waltzek, et al are shown [11]. Malacoherpesviridae contains Ostreid Herpesvirus-1 (OsHV-1) as its sole member, in the genus Ostreavirus [12].…”
Section: Ostreid Herpesvirusmentioning
confidence: 99%
“…The most previously researched Alloherpesvirus, channel catfish herpesvirus (Ictalurid herpesvirus 1 (IcHV-1), CCV) infects channel catfish but also blue catfish [8] and possibly other catfish species or subspecies while IcHV-2 was detected in black bullhead (Ameiurus melas) and in channel catfish (Ictalurus punctatus) [9]. Members of the salmonivirus group are known to often infect more than one species: salmonid herpesvirus 1 (SaHV-1) have been detected in rainbow trout (Ocorhynchus mykiss) [3] but also in Chum salmon (O. keta) and Chinook salmon (O. kisutch) [10]. SaHV-2 was considered to infect all salmonid species [3] and SaHV-3 was detected in different fish and hybrids of the genus Salvelinus [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the salmonivirus group are known to often infect more than one species: salmonid herpesvirus 1 (SaHV-1) have been detected in rainbow trout (Ocorhynchus mykiss) [3] but also in Chum salmon (O. keta) and Chinook salmon (O. kisutch) [10]. SaHV-2 was considered to infect all salmonid species [3] and SaHV-3 was detected in different fish and hybrids of the genus Salvelinus [3,11,12]. In addition to cyprinid herpesviruses 1,2 and 3 the eel herpesvirus (HVA, AngHV-1) is also included in the genus Cyprinivirus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation